Enhancing students’ critical thinking skills: Developing a biology practicum module using the PjBL model by integrating local Banana Goroho - Rengkuan , Mariana; Howan , Dian Herlinda Octorina; Leasa, Marleny (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
The lack of integration of project-based learning (PjBL) in nutrition education, especially in the context of local foods that have great potential but have not been widely explored, especially the use of (Musa acuminafe) as a practicum material, which is an alternative carbohydrate source typical of the Minahasa region. This study aims to develop a practicum module that enhances thinking skills using the PjBL model by testing the nutritional content of local foods of the Minahasa community (local banana Goroho/Musa acuminafe). This study employed a research and development (R&D) approach using the ASIE model (Analyse, Design, Implement, and Evaluate). The research subjects were undergraduate Biology students at Manado State University, with a sample of 30 students enrolled in the first semester of the 2024/2025 academic year. The research instruments included module validation sheets, student response questionnaires, and critical thinking skills tests to assess the effectiveness of the developed practicum module with the N-Gain score. The validation results from material and media experts show that the developed module is very valid, with scores reaching 96.166% and 95.6%, respectively. Furthermore, testing of students' critical thinking skills showed very good results, with an average score reaching 85.51%. In addition, student responses to this practicum module were also very positive, with an average score of 91.074%, which indicates a very practical category. These findings confirm the module's effectiveness in enhancing students' critical thinking skills (N-Gain=0.71, high category) and its relevance in the context of locally-based nutrition education. This research significantly contributes to the development of innovative and community-relevant learning methods and can serve as a reference for further research in education and nutrition.